0.002(3-k)+0.07(k-3)=1

Simple and best practice solution for 0.002(3-k)+0.07(k-3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.002(3-k)+0.07(k-3)=1 equation:


Simplifying
0.002(3 + -1k) + 0.07(k + -3) = 1
(3 * 0.002 + -1k * 0.002) + 0.07(k + -3) = 1
(0.006 + -0.002k) + 0.07(k + -3) = 1

Reorder the terms:
0.006 + -0.002k + 0.07(-3 + k) = 1
0.006 + -0.002k + (-3 * 0.07 + k * 0.07) = 1
0.006 + -0.002k + (-0.21 + 0.07k) = 1

Reorder the terms:
0.006 + -0.21 + -0.002k + 0.07k = 1

Combine like terms: 0.006 + -0.21 = -0.204
-0.204 + -0.002k + 0.07k = 1

Combine like terms: -0.002k + 0.07k = 0.068k
-0.204 + 0.068k = 1

Solving
-0.204 + 0.068k = 1

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '0.204' to each side of the equation.
-0.204 + 0.204 + 0.068k = 1 + 0.204

Combine like terms: -0.204 + 0.204 = 0.000
0.000 + 0.068k = 1 + 0.204
0.068k = 1 + 0.204

Combine like terms: 1 + 0.204 = 1.204
0.068k = 1.204

Divide each side by '0.068'.
k = 17.70588235

Simplifying
k = 17.70588235

See similar equations:

| -.02-.02(3-5p)=.06(p-4)-.08 | | -375p=1050 | | (4)x*x+2x=17 | | y=17-2(4) | | x(5x-2)+x(3x-6)=(8x+4)(x-1) | | 4x^2+8x=11 | | 4x^2-8x=11 | | 8=-(2r-4) | | -16lnx=-4In | | 18y-21=15y+3 | | .35w=280 | | 2(x^2)-15x-1=0 | | 0.8t=24 | | 32=2-5(-4n+6) | | 32=2-5(4n+6) | | 8+3g-2=-27 | | 18=5+4m-2 | | (6x+2)(x-3)=9 | | -3(2a-1)=1 | | 11(6x+6)+11x=3-2(x+8) | | 4x+8x=60 | | 3(x-15)=11 | | -9(v+4)+4v+6=8v+9 | | 2x^2=160 | | M-4m+2m-6= | | (2x^2)-15x-1=0 | | 4x+5x=60 | | 8(x+9)+4=8x+7 | | 10-9(1-10p)=-28+90p | | 10-9-90p=-28+90p | | 10-3w+5=9w+3-6w | | x+3-2=0 |

Equations solver categories